Open veins of Latin America - "Galeano, Eduardo" (Gurgaon, 2010)
Many years ago, when I was young and still believed that the world could be shaped according to our best intentions and hopes, someone gave me a book with a yellow cover that I devoured in two days with such emotion that I had to read it again a couple more times to absorb all its meaning: Open Veins of Latin America, by Eduardo Galeono.
Keywords: Latin America-Economic history